Summative Evaluation of ICT-Based Learning Media - Mertasari, Ni Made Sri (Journal of Education Reseach and Evaluation, 2022)
Prospective teacher students have been heavily involved in developing ICT-based learning media. Various forms of media have been produced, such as multimedia, hypermedia, web, video, animation, or presentation. Until now, not all media developed have undergone a summative evaluation but only arrived at a formative evaluation. One of the reasons is the lack of references. This study aims to formulate a summative evaluation model of ICT-based learning media developed by prospective teacher students using quantitative and qualitative descriptive approaches. The study began with observations of student research reports to examine the summative evaluation model used. The information is then discussed in a focus group discussion involving relevant experts and practitioners. The study found that the summative evaluation of ICT-based learning media could be done through a quasi-experimental survey or case study. Quasi-experimental methods that can be applied are nonequivalent control group design, factorial design, counterbalanced design, and time series design. The format was obtained mainly considering limited time, a place for testing, and opportunities to be involved in the class. Either quasi-experiments, surveys, or case studies can be carried out by students in collaboration with relevant teachers when students do teaching practicum at school and then mature when students do research.